Nutrition behavior of the middle-aged and elderly: Compliance with dietary recommendations of the food pyramid. Issue 3 (June 2016) - Gille, Doreen; Bütikofer, Ueli; Chollet, Magali; Schmid, Alexandra; Altintzoglou, Themistoklis; Honkanen, Pirjo; Stoffers, Helena; Walther, Barbara; Piccinali, Patrizia
Summary: Background & aims: During the aging process, human physiology changes noticeably, mostly to the disadvantage of the individual. A healthy lifestyle that includes sufficient physical activity as well as a balanced and diverse diet contributes to healthy aging. One key factor that elderly people need to be aware of is compliance with nutritional recommendations. There is very little data concerning eating patterns, consumption behavior, and compliance with food guides (food pyramid) and nutritional recommendations among the Swiss, particularly for the middle-aged and elderly. The objective of this study was to gather new and representative information about these issues, concentrating on people aged 50+ and living in Switzerland. Methods: A questionnaire in online and written form was distributed to a representative sample of middle-aged and elderly people living in Switzerland. Results: In total, 632 people returned the survey. Of those respondents, 71% knew the Swiss Food Pyramid but only 38% said they comply with it. Based on self-reports, only a few participants met the recommendations for the different food groups listed in the food pyramid, whether in the pyramid-comply or pyramid-non-comply group. Conclusion: The survey shows that the middle-aged and elderly living in Switzerland need more nutritional guidance to help them to meet dietary recommendations. As usage and understanding of food guides seem limited among this population group, new tools must be explored for transfer of recommendations to real applications.